Detrimental Immediate- and Medium-Term Clinical Effects of Right Ventricular Pacing in Patients With Myocardial Fibrosis. (18th May 2021) - Saunderson, Christopher E.D.; Paton, Maria F.; Brown, Louise A.E.; Gierula, John; Chew, Pei G.; Das, Arka; Sengupta, Anshuman; Craven, Thomas P.; Chowdhary, Amrit; Koshy, Aaron; White, Hazel; Levelt, Eylem; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Long-term right ventricular (RV) pacing leads to heart failure or a decline in left ventricular (LV) function in up to a fifth of patients. We aimed to establish whether patients with focal fibrosis detected on late gadolinium enhancement cardiovascular magnetic resonance (CMR) have deterioration in LV function after RV pacing. Methods: We recruited 84 patients with LV ejection fraction ≥40% into 2 observational CMR studies. Patients (n=34) with a dual-chamber device and preserved atrioventricular conduction underwent CMR in 2 asynchronous pacing modes (atrial asynchronous and dual-chamber asynchronous) to compare intrinsic atrioventricular conduction with forced RV pacing. Patients (n=50) with high-grade atrioventricular block underwent CMR before and 6 months after pacemaker implantation to investigate the medium-term effects of RV pacing. Results: The key findings were (1) initiation of RV pacing in patients with fibrosis, compared with those without, was associated with greater immediate changes in both LV end-systolic volume index (5.3±3.5 versus 2.1±2.4 mL/m 2 ; P <0.01) and LV ejection fraction (−5.7±3.4% versus −3.2±2.6%; P =0.02); (2) medium-term RV pacing in patients with fibrosis, compared with those without, was associated with greater changes in LV end-systolic volume index (8.0±10.4 versus −0.6±7.3 mL/m 2 ; P =0.008) and LV ejection fraction (−12.3±7.9% versus −6.7±6.2%; P =0.012); (3) patients with fibrosis did not experience an improvement in quality of life, biomarkers, or functional class after pacemaker implantation; (4) after 6 months of RV pacing, 10 of 50 (20%) patients developed LV ejection fraction <35% and were eligible for upgrade to cardiac resynchronization according to current guidelines. All 10 patients had fibrosis on their preimplant baseline scan and were identified by >1.1 g of fibrosis with 90% sensitivity and 70% specificity. Conclusions: Fibrosis detected on CMR is associated with immediate- and medium-term deterioration in LV function following RV pacing and could be used to identify those at risk of heart failure before pacemaker implantation.